PENGARUH KEUNIKAN PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA SEBLAK PRASMANAN MUNAWAROH DI SITUBONDO - Ali Gufron; Dassucik Dassucik; Ahmad Hafas Rasyidi (MANAJEMEN, 2025)
The culinary world in Indonesia continues to develop rapidly, with a wide variety of foods that are very popular with the public. As a result, many producers are opening up broad business opportunities and attracting the attention of consumers in Indonesia. Many new food brands are beginning to appear, each with its own uniqueness, making business competition in the culinary world increasingly fierce. The purpose of this study is to determine the influence of product uniqueness and price on consumer satisfaction at Munawaroh's  buffet in Situbondo. This study uses a quantitative approach. Quantitative research is a type of research that is systematic, planned, and clearly structured, from formulation to research design.  Based on the SPSS calculations above, it can be concluded that the correlation coefficient of 0.504 indicates the influence of product uniqueness and price on consumer satisfaction. In this case, the number of research respondents was 100 respondents. The R table value is obtained by calculating the degree of freedom (df) = 100 – 2 = 98, with df = 98 and alpha = 0.05, resulting in an R table value of 0.198. Therefore, r calculated > r table, 0.504 > 0.198, meaning the null hypothesis is rejected and the alternative hypothesis Ha is accepted, indicating that there is an influence of product uniqueness and price on consumer satisfaction, representing a high correlation. The calculated t-value for product uniqueness is 3.263, and the t-table value is 1.980. This means that the t-table value is greater than the calculated t-value (3.263 < 1.980). Therefore, it can be concluded that there is an influence of the product uniqueness variable on consumer satisfaction, so Ha is accepted. The calculated t-value for price is 3.662 and the table t-value is 1.980, meaning that the table t-value is greater than the calculated t-value (3.662 < 1.980). Therefore, it can be concluded that there is a simultaneous effect of the price variable on consumer satisfaction, so Ha is accepted and Ho is rejected.